Evaluation of the epistemic state of the speaker/author. Issue 6 (June 2018) - Clifton, Charles; Frazier, Lyn
Language users are sensitive to their language's grammatical requirements, the plausibility of the situation described and the information shared by speaker and listener. We propose that they are also sensitive to whether an author is likely to be in a state of knowledge that actually supports the assertion being made. Failure to be in such a state reduces the naturalness of the assertion. Consistent with this proposal, sentences with a disjoined noun phrase are judged to be less natural than their conjunctive counterparts, presumably because the author of a disjunctive sentence must know that an event took place but not know which of the two individuals was the agent. This unlikely state of knowledge reduces the naturalness of the sentence. The results of three experiments indicate that providing evidence that the speaker could be in an unlikely epistemic state reduces the disjunction penalty; a fourth extends the demonstration of the penalty from coordinated noun phrases to coordinated verb phrases. We also present one experiment that explores the possibility that disjunction penalty is due to the unexpectedness of a disjunction. These findings demonstrate that language users evaluate linguistic input in light of the epistemic state of its author.